2011
DOI: 10.1074/jbc.m111.274100
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Receptor II Is a Novel Mediator of Endothelial Nitric-oxide Synthase Activation

Abstract: Activation of bone morphogenetic protein (BMP) receptor II (BMPRII) promotes pulmonary artery endothelial cell (PAEC) survival, proliferation, and migration. Mutations to BMPRII are associated with the development of pulmonary arterial hypertension (PAH). Endothelial dysfunction, including decreased endothelial nitric-oxide synthase (eNOS) activity and loss of bioactive nitric oxide (NO), plays a prominent role in the development of PAH. We hypothesized that stimulation of BMPRII promotes normal PAEC function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 31 publications
4
78
1
Order By: Relevance
“…These findings are consistent with the observation that BMP ligands enhance NO production and induce phosphorylation of Ser1177 eNOS in cultured PECs 34,54 and that there are decreased eNOS activity and pSer1177 eNOS levels in the pulmonary vasculature of Bmpr2 ΔEx2/+ mutant mice and in PECs from ΔEx2/+ (ΔE2/+) mice. A, Western blots of lung lysates, demonstrating phosphorylated S1177 and T495 (pS1177 and pT495, respectively) and total eNOS levels and β-actin.…”
Section: While There Was a Spread In Ph Responses Between Mice Bmpr2supporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with the observation that BMP ligands enhance NO production and induce phosphorylation of Ser1177 eNOS in cultured PECs 34,54 and that there are decreased eNOS activity and pSer1177 eNOS levels in the pulmonary vasculature of Bmpr2 ΔEx2/+ mutant mice and in PECs from ΔEx2/+ (ΔE2/+) mice. A, Western blots of lung lysates, demonstrating phosphorylated S1177 and T495 (pS1177 and pT495, respectively) and total eNOS levels and β-actin.…”
Section: While There Was a Spread In Ph Responses Between Mice Bmpr2supporting
confidence: 91%
“…25,54 However, these findings also suggest that the differential regulation of pSer1177 eNOS is unlikely to account for differences in PH severity in Bmpr2 +/− and Bmpr2…”
Section: While There Was a Spread In Ph Responses Between Mice Bmpr2mentioning
confidence: 82%
“…Additionally, all glassware and plastics used for cell culture were opened in a sterile work environment. This protocol is detailed to give investigators the ability to study more reliably the role of pulmonary endothelial cells in lung vascular diseases (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…This was shown to be due to decreased endothelial nitric oxide synthase (eNOS) expression and activity in the pulmonary vasculature of hypoxic Bmp2+/-but not Bmp4+/-mice. It was also shown that activation of BMPRII promotes pulmonary artery EC (PAEC) survival, proliferation, and migration by activating eNOS [125]. BMP2 and BMP4 were shown to stimulate eNOS phosphorylation resulting in increased eNOS activity.…”
Section: Vascular Tone and Tgf Signalingmentioning
confidence: 99%